Model-driven software development in the institutional repositories (2014)
The Institutional Repositories (IR) have been consolidated into the academy, the proof of this is the growth in number of records in existing directories made by various means, such as self-archiving by authors and the incorporation of material by librarians. In this paper, a bibliographic survey about the use of the Model-Driven Software Development approach is done (MDD) in the IR systems in order to establish a relationship between them. The MDD is a paradigm for building software that assigns a central role to the models and originates models that range from the most abstract to the most concrete. This paradigm also provides a framework that allows the interested ones to share their points of view and directly manipulate the representations of the domain entities from IR. In conclusion, the monitoring of the various researches, and what is expressed here, allow to encourage the implementation of software for IR.